DIGITAL TRANSFORMATION AND THE NEW APPROACHES IN TOURISM - Umidakhon Narzullayeva (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
The last decade has seen major changes in the travel distribution landscape. First, the Internet began a revolution and dramatically changed the way the tourism industry works. The spreading of smartphones and social media has created further both chaos and new opportunities. While opening up new opportunities for growth, these developments also created new operational challenges. Hoteliers and other business leaders operating in the travel industry have needed to follow the latest digital trends. Failure to do so can result in competitors gaining a competitive advantage.